2017
DOI: 10.1080/09537104.2017.1294680
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation test for evaluation of antiplatelet treatment in patients with coronary artery disease after percutaneous coronary intervention

Abstract: To study the possibility of using thrombin generation tests in platelet-rich and platelet-poor plasma for evaluation of dual antiplatelet therapy efficacy in patients with coronary artery disease (CAD), following percutaneous coronary intervention. Venous blood was analyzed from CAD patients aged 53-75 years who had undergone percutaneous coronary intervention with stenting within one year and had been receiving standard doses of clopidogrel and aspirin (75 and 75-100 mg per day, respectively). The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Antiplatelet medications have, however, been shown to be without effect on thrombin generation. 38 Also, as AAS abuse is characterized by intake of several compounds taken intermittently, it is difficult to transfer our results to other cohorts of AAS abusers.…”
Section: Discussionmentioning
confidence: 93%
“…Antiplatelet medications have, however, been shown to be without effect on thrombin generation. 38 Also, as AAS abuse is characterized by intake of several compounds taken intermittently, it is difficult to transfer our results to other cohorts of AAS abusers.…”
Section: Discussionmentioning
confidence: 93%
“…The function of coagulation factor can be reflected by R value, K value and MA value. When R value and K value are increased and MA value is decreased, coagulation factor and platelet coagulation acti vity are both decreased (21). It is indicated that the overall coagulation function of patients was better in the experimental group than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Even though antiplatelet therapy, like aspirin and clopidogrel, do not affect coagulation factors, the effect of 10.3389/fcvm.2022.1033416 these therapies on thrombin generation were studied in PRP as well as PPP. A case-control study showed that patients with CAD followed by PCI who were treated with standard dosage of dual antiplatelet therapy with aspirin and clopidogrel had significant longer time to thrombin peak, decreased thrombin peak height and ETP than controls in PRP (181). Velocity of thrombin generation was most impaired in patients.…”
Section: Antiplatelet Therapymentioning
confidence: 99%